El Partido Socialista argentino, 1896-1912 Una historia social y política - Poy, Lucas (Ariadna Ediciones, 2020)
Social and political history of the origins of the Socialist party of Argentina towards the beginning of the century until the enactment of the electoral law Sáenz Peña